Phosphorus-containing (meth) acryloyl composition, method for producing same, flame-retardant resin composition, prepreg, and use thereof

By mixing phosphorus-containing (meth)acryloyl compounds of different chemical structures and reacting with quinone compounds to form hydroxyl-containing phosphorus compounds, the problem of precipitation of halogen-free flame retardant in solvent dissolution is solved, and low dielectricity is achieved Characteristics and stable flame retardant effect.

CN119176840APending Publication Date: 2024-12-24NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410783886.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-22
Filing Date
2024-06-18
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing halogen-free flame retardant is prone to precipitation during solvent dissolution, resulting in uneven resin composition and difficult to meet the needs of low dielectric constant and low dielectric loss tangent.

Method used

By mixing phosphorus-containing (meth)acryloyl compounds of different chemical structures, a composition is formed, precipitation is inhibited, and reaction with quinone compounds to form a phosphorus compound containing hydroxyl groups is improved, and solvent solubility and flame retardancy are improved.

Benefits of technology

The stability and uniformity in the solvent dissolved state are achieved, and low dielectric constant, low dielectric loss tangent and excellent heat resistance are shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176840A_ABST
    Figure CN119176840A_ABST
Patent Text Reader

Abstract

Provided are: a phosphorus-containing (meth) acryloyl composition which is capable of imparting halogen-free flame retardancy, has a low dielectric constant and a low dielectric loss tangent, has excellent solvent solubility, does not readily precipitate, and has significantly improved stability; a method for producing the phosphorus-containing (meth) acryloyl composition; a flame-retardant resin composition; a prepreg; the phosphorus-containing (methyl) acryloyl composition is a composition of phosphorus-containing (methyl) acryloyl compounds represented by a general formula (1), and the phosphorus-containing (methyl) acryloyl composition contains at least two phosphorus-containing (methyl) acryloyl compounds with different chemical structures. In the general formula (1), R1, R2 and R3 independently represent a hydrogen atom, a hydroxyl group or a group represented by-R, and R represents a hydrocarbon group having 1-40 carbon atoms; r1 and R2 can be the same or different, and can also form a cyclic structure together with phosphorus atoms; n is 0 or 1; x represents an aromatic hydrocarbon group having 6-20 carbon atoms, and m is 1-3. [chemical] # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a phosphorus-containing (meth)acryloyl compound which exhibits flame retardancy and excellent solvent dissolution stability and can be preferably used as a reactive flame retardant, and more particularly to a phosphorus-containing (meth)acryloyl composition and a method for producing the same, a flame retardant resin composition, a prepreg, and applications thereof. Background Art

[0002] Resin compositions for electronic devices, particularly circuit boards, need to be flame retardant. Due to concerns about the safety of halogenated compounds generated during combustion and the possibility of fatal accidents due to the generated smoke, it is desired that the flame retardant be halogen-free. For example, a resin composition having flame retardancy provided by a phosphorus-containing resin as disclosed in Patent Document 1 has been proposed.

[0003] Furthermore, as a halogen-free flame retardant, a reactive flame retardant does not cause environmental pollution due to bleeding or dissolution and a decrease in glass transition temperature due to plasticization, which are disadvantages of additive flame retardants. Therefore, the demand for reactive flame retardants is increasing.

[0004] On the other hand, in order to improve high-speed communication technology, resin compositions are required to have low dielectric constants and low dielectric loss tangents, and there is a shift from epoxy resins, which are the mainstream for circuit board applications, to resins having free radical polymerizable functional groups such as maleimide resins and vinyl resins disclosed in Patent Documents 2 and 3.

[0005] Maleimide resins and vinyl resins also need to be given halogen-free flame retardancy. For example, Patent Document 4 discloses a phosphorus-containing vinyl benzyl ether compound obtained by reacting a specific phosphorus-containing phenol compound with a vinyl benzyl halide, and Non-Patent Document 1 discloses a polyfunctional (meth)acryloyl compound using an adduct of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, DOPO) and quinones. However, when impregnating glass cloth, there is a problem that the impregnation is difficult or the resin with a high flame retardant effect is uneven due to the precipitation of the phosphorus-containing compound in the resin composition dissolved in the solvent.

[0006] As described above, as a halogen-free flame retardant having a radically polymerizable functional group, a reactive flame retardant showing a low dielectric constant and a low dielectric loss tangent and excellent solvent dissolution stability is required.

[0007] [Prior art literature]

[0008] [Patent Document]

[0009] [Patent Document 1] Japanese Patent Application Laid-Open No. 11-279258

[0010] [Patent Document 2] Japanese Patent Application Publication No. 2017-137492

[0011] [Patent Document 3] Japanese Patent Publication No. 2004-123873

[0012] [Patent Document 4] Japanese Patent Application Publication No. 2020-147519

[0013] [Non-patent literature]

[0014] [Non-patent document 1] Industrial and Engineering Chemistry Research (Ind. Eng. Chem. Res.) 2013, 52, 12855-12864 Summary of the invention

[0015] [Problems to be solved by the invention]

[0016] The problem to be solved by the present invention is to provide a phosphorus-containing (meth)acryloyl compound composition which can impart halogen-free flame retardancy, has low dielectric constant and dielectric loss tangent, is excellent in solvent solubility, is not prone to precipitation, and has dramatically improved stability.

[0017] [Technical means to solve the problem]

[0018] The present invention has been studied intensively to solve the above-mentioned problems, and as a result, it has been found that by preparing a composition in which two or more compounds having different structures of phosphorus-containing (meth)acryloyl compounds are mixed, precipitation (crystallization) from solvent dissolution can be significantly suppressed, and flame retardancy, heat resistance and dielectric properties are also excellent, thereby completing the present invention.

[0019] That is, the present invention is a phosphorus-containing (meth)acryl composition.

[0020] The composition is a phosphorus-containing (meth)acryloyl compound composition represented by the general formula (1), wherein the composition comprises at least two phosphorus-containing (meth)acryloyl compounds having different chemical structures.

[0021] [Chemistry 1]

[0022]

[0023] (In general formula (1), R 1 , R 2 , R 3 are independently hydrogen, hydroxyl or a group represented by -R, where R is a hydrocarbon group having 1 to 40 carbon atoms; R 1 , R 2may be the same or different, and may form a ring structure together with the phosphorus atom; n is 0 or 1; X represents an aromatic hydrocarbon group having 6 to 20 carbon atoms, and m is 1 to 3)

[0024] The present invention is a method for producing a phosphorus-containing composition, wherein at least two hydroxyl-containing phosphorus compounds represented by the general formula (2) are reacted with (meth)acrylic acid, (meth)acrylic anhydride or (meth)acryloyl halide compounds, and the two or more hydroxyl-containing phosphorus compounds are (meth)acryloylated.

[0025] [Chemistry 2]

[0026]

[0027] (R in general formula (2) 1 , R 2 , X, n, and m have the same meanings as in the general formula (1)

[0028] The present invention is a method for producing a phosphorus-containing (meth)acryloyl composition, wherein a phosphorus-containing compound represented by the general formula (3) is reacted with a quinone compound to obtain two or more hydroxyl-containing phosphorus compounds, and then the obtained two or more hydroxyl-containing phosphorus compounds are (meth)acrylated.

[0029] [Chemistry 3]

[0030]

[0031] (R in general formula (3) 1 , R 2 , n has the same meaning as in the general formula (1))

[0032] The present invention relates to a flame-retardant resin composition, a prepreg, or a resin sheet, a cured product, and a laminate for an electronic circuit substrate. The flame-retardant resin composition is formed by mixing one or more thermosetting resins or thermoplastic resins in a phosphorus-containing (meth)acryl composition. The prepreg is formed by mixing the flame-retardant resin composition in a fibrous substrate to semi-cure the flame-retardant resin composition. The resin sheet is formed by applying the flame-retardant resin composition to a resin film to semi-cure the flame-retardant resin film. The cured product is formed by curing the flame-retardant resin composition, the prepreg, and the resin sheet. The laminate for an electronic circuit substrate contains the flame-retardant resin composition as an essential component.

[0033] [Effects of the Invention]

[0034] The phosphorus-containing (meth)acryl composition of the present invention has two or more different structures, and is stable in a solvent-dissolved state, does not precipitate during the adjustment process, and maintains uniform properties even during operations such as impregnation into a substrate such as glass cloth or coating on a sheet, thereby showing stable flame retardancy. The obtained cured product shows a low dielectric constant and dielectric loss tangent, and is also excellent in heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 2 is shown.

[0036] Figure 2 The HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 6 is shown.

[0037] Figure 3 The HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 7 is shown.

[0038] Figure 4 The HPLC chart of the phosphorus-containing methacryloyl compound obtained in Example 8 is shown.

[0039] Figure 5 The HPLC chart of the phosphorus-containing methacryloyl compound obtained in Comparative Example 2 is shown. DETAILED DESCRIPTION

[0040] Hereinafter, the present invention will be described in detail.

[0041] In the description of the present invention, the names of acrylic resins, acrylic compounds, or acrylate compounds are usually referred to as "(meth)acryl", "acrylic acid" and "methacrylic acid" are sometimes referred to as "(meth)acrylic acid", "acrylate" and "methacrylate" are sometimes referred to as "(meth)acrylate", and "acrylate" and "methacrylate" are sometimes referred to as "(meth)acrylate".

[0042] The phosphorus-containing (meth)acryl composition of the present invention is a composition of phosphorus-containing (meth)acryl compounds represented by the general formula (1), wherein the composition contains at least two phosphorus-containing (meth)acryl compounds having different chemical structures.

[0043] [Chemistry 4]

[0044]

[0045] The phosphorus-containing (meth)acryl composition of the present invention comprises at least two phosphorus-containing (meth)acryl compounds of different chemical structures, and the solvent solubility is improved by containing 1 area % or more of each compound. The content of each compound is more preferably 10 area % or more, and further preferably 15 area % or more. The content (area %) of each component can be measured by high performance liquid chromatography (HPLC).

[0046] In the case of a two-component system including two components having different chemical structures, each component is preferably contained in the range of 30 area % to 70 area %, more preferably 40 area % to 60 area %.

[0047] In the case of a three-component system including three components having different chemical structures, each component is preferably contained in the range of 10 area % to 60 area %, more preferably 15 area % to 50 area %.

[0048] In the case of a four-component system including four components having different chemical structures, each component is preferably contained in the range of 10 area % to 50 area %, more preferably 10 area % to 45 area %.

[0049] When five or more components with different chemical structures are included, each component is preferably contained in the range of 1 area % to 50 area %, more preferably 1 area % to 40 area %.

[0050] Here, R 1 , R 2 It is preferably a phenyl group, and may have an alkyl group having 1 to 6 carbon atoms or a phenyl group as a substituent. 3 Preferably, it is an alkyl group having 1 to 3 carbon atoms. X is a group derived from a quinone compound, and is preferably an aromatic ring group such as benzene, toluene, xylene, naphthalene, etc., and each aromatic ring may have an alkyl group having 1 to 6 carbon atoms or a phenyl group as a substituent. The same applies to the following formulae.

[0051] The phosphorus content of the phosphorus-containing (meth)acryl composition of the present invention is preferably 1 to 20% by weight, more preferably 3 to 10% by weight, based on the solid content.

[0052] The hydroxyl-containing phosphorus compound represented by the general formula (2) can be synthesized by the reaction of an organic phosphorus compound having active hydrogen directly bonded to a phosphorus atom with a quinone compound, and by a known method disclosed in Japanese Patent Laid-Open No. 61-236787, Japanese Patent Laid-Open No. 05-331179, Japanese Patent Laid-Open No. 05-39345, etc. Examples of organophosphorus compounds include dimethyl phosphine, diethyl phosphine, and diphenyl phosphine; phosphine oxides include dimethyl phosphine oxide, diethyl phosphine oxide, diphenyl phosphine oxide, methyl phenyl phosphite, and tert-butyl phenyl phosphine oxide; and phosphates include diethyl hydrogen phosphite, bis(2-ethylhexyl) hydrogen phosphite, dilauryl hydrogen phosphite, dioleyl hydrogen phosphite, diphenyl hydrogen phosphite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (manufactured by HCA Sanguang), 8-benzyl-9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (manufactured by Bz-HCA Sanguang), etc. However, the present invention is not limited to these, and two or more thereof may be used. Specific examples of quinone compounds include 1,4-benzoquinone, 1,2-benzoquinone, toluoquinone, phenylbenzoquinone, 1,4-naphthoquinone, 1,2-naphthoquinone, hydroxynaphthoquinone, methylnaphthoquinone, etc. These quinones may be used alone or in combination of two or more, and are not limited thereto.

[0053] [Chemistry 5]

[0054]

[0055] Regarding the hydroxyl-containing phosphorus compound represented by the general formula (2), it is important to use two or more compounds with different chemical structures in combination, and a plurality of different single compounds can also be prepared. However, there is also a method of obtaining a hydroxyl-containing phosphorus compound as a mixture of two or more by selecting an organic phosphorus compound represented by the general formula (3) and a quinone compound.

[0056] [Chemistry 6]

[0057]

[0058] For example, when toluenequinone is used as the quinone compound, isomers in which the methyl group is located at the ortho-position, the para-position, or the meta-position can be obtained. Therefore, a mixture of two or more types can be easily obtained, and solvent solubility can be improved.

[0059] The reaction between the organophosphorus compound and the quinone compound is carried out by dissolving the organophosphorus compound in an inert solvent and adding the quinone compound.

[0060] The molar ratio of the quinone compound to the organic phosphorus compound is preferably in the range of 1.2 mol to 0.7 mol, and more preferably in the range of 1.0 mol to 0.9 mol.

[0061] The hydroxyl-containing phosphorus compound represented by the general formula (2) can be synthesized by reacting an organic phosphorus compound having active hydrogen directly bonded to a phosphorus atom represented by the general formula (3) with a quinone compound. Through the above reaction, a structure in which two phosphorus atoms represented by the following general formula (4) are added to the quinone compound may be produced as a by-product. However, this is not a compound that hinders the effect of the present invention and there is no problem even if it is included.

[0062] [Chemistry 7]

[0063]

[0064] Furthermore, the hydroxyl-containing phosphorus compound represented by the general formula (2) may be a commercially available product. For example, diphenylphosphinylhydroquinone (PPQ, manufactured by Hokko Chemical Industry Co., Ltd.), 10-(2,5-dihydroxyphenyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (HCA-HQ manufactured by Sanko Co., Ltd.), 10-(2,5-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (HCA-NQ manufactured by Sanko Co., Ltd.), 1,4-cyclooctylenephosphonylhydroquinone, 1,5-cyclooctylenephosphonylhydroquinone (CPHO-HQ manufactured by Nippon Chemical Industry Co., Ltd.), etc. may be purchased and combined to prepare two or more hydroxyl-containing phosphorus compounds.

[0065] The reaction of the hydroxyl group-containing phosphorus compound with (meth)acrylic acid, (meth)acryloyl halide or (meth)acrylic anhydride is not particularly limited and can be carried out in the same manner as a normal (meth)acryloylation reaction of an alcohol compound or a phenol compound.

[0066] By using multiple types of (meth)acrylic acid, (meth)acrylic halide or (meth)acrylic anhydride used in the (meth)acrylation reaction, as the phosphorus-containing (meth)acrylic compound represented by the general formula (1), a phosphorus-containing (meth)acrylic composition containing two or more different chemical structures can be prepared.

[0067] For example, when (meth)acrylic acid is used, it can be produced by condensing a hydroxyl-containing phosphorus compound with (meth)acrylic acid in an amount of 1 to 10 times the amount of hydroxyl group in the presence of a strong acid catalyst such as sulfuric acid, p-toluenesulfonic acid, or methanesulfonic acid. This reaction needs to be carried out while removing the condensation water produced as a byproduct to the outside of the system, so a hydrocarbon solvent such as toluene that azeotropes with water is used as a reaction solvent, and the reaction solution is heated to about 70°C to 140°C.

[0068] Furthermore, the phosphorus-containing (meth)acryloyl compound of the present invention can be obtained by reacting a hydroxyl-containing phosphorus compound with a (meth)acryloyl halide or (meth)acrylic anhydride. Usable (meth)acryloyl halides include: acryloyl halides such as acryloyl fluoride, acryloyl chloride, acryloyl bromide, and acryloyl iodide; and methacryloyl halides such as methacryloyl fluoride, methacryloyl chloride, methacryloyl bromide, methacryloyl iodide, methylenebutyryl chloride, methylenevaleryl chloride, methylenehexanoyl chloride, methylenecyclohexaneacetyl chloride, and methylenephenylacetyl chloride.

[0069] In the practice of the present invention, as the (meth)acrylic acid halide and (meth)acrylic anhydride, one or a mixture of two or more may be used. In the present invention, from the aspect of easy availability, (meth)acrylic acid chloride and / or (meth)acrylic anhydride are preferably used.

[0070] The amount of (meth)acrylic halide or / and (meth)acrylic anhydride used is 0.8 mol to 5 mol, preferably 0.95 mol to 4 mol, relative to 1 mol of the hydroxyl group of the phosphorus-containing phenol compound used as a raw material. When the amount of (meth)acrylic halide or / and (meth)acrylic anhydride used is less than the above range, the heat resistance of the obtained phosphorus-containing (meth)acrylic compound decreases, and the residual amount of hydroxyl groups increases, so the dielectric properties deteriorate, which is not preferred. When the amount used exceeds the above range, the reactor efficiency decreases and the cost increases, which is not preferred.

[0071] When a (meth)acryloyl halide is used, hydrogen halide corresponding to the (meth)acrylic acid halide used is generated as a by-product. Therefore, it is preferable to use a basic compound together to carry out the reaction while capturing the generated hydrogen halide. The basic compound is not particularly limited, and examples thereof include aliphatic amines such as trimethylamine, triethylamine, diisopropylethylamine, tri-n-propylamine, triisopropylamine, tributylamine, N-methyl-diethylamine, N-ethyl-dimethylamine, and N-ethyl-dipentylamine; aromatic amines such as N,N-dimethylaniline and diethylaniline; alicyclic amines such as N,N-dimethyl-cyclohexylamine and N,N-diethyl-cyclohexylamine; heterocyclic amines such as N,N-dimethylaminopyridine, N-methylmorpholine, diazabicycloundecene (DBU), diazabicyclononene (DBN), N-methylpyridine, N-methylpyrrolidine, and N-methylimidazole; diamines such as tetramethylethylenediamine and triethylenediamine, etc. In particular, aliphatic amines such as trimethylamine and triethylamine, and pyridine are preferred from the perspective of easy availability.

[0072] The amount of the basic compound used is, for example, 0.8 to 7 moles, preferably about 0.95 to 5 moles, relative to 1 mole of the hydroxyl group of the phosphorus-containing phenol compound used as a raw material. When the amount of the tertiary amine used is below the above range, the hydrogen halide cannot be completely captured, which may cause corrosion of the reaction device, and when it exceeds the above range, there is a tendency for the cost to become high.

[0073] When the reaction is carried out using (meth)acrylic anhydride, a catalyst may not be used, but when the reaction is difficult to proceed, an ester catalyst, an acid catalyst, a base catalyst, or a Lewis acid catalyst may be used. Here, as an ester catalyst, sodium acetate, potassium propionate, sodium (meth)acrylate, and other alkali metal salts of lower carboxylic acids such as sodium and potassium may be exemplified. Moreover, as an acid catalyst, inorganic acids such as sulfuric acid and boric acid may be exemplified; organic acids such as methanesulfonic acid and p-toluenesulfonic acid may be exemplified. Moreover, as a base catalyst, if it is an organic base, nitrogen-containing aliphatic compounds such as triethylamine and triethylenediamine may be exemplified; nitrogen-containing aromatic heterocyclic compounds such as pyridine, 4-(dimethylamino)pyridine, and N-methylimidazole may be exemplified. Moreover, as a Lewis acid catalyst, aluminum chloride, zinc chloride, etc. may be exemplified.

[0074] The amount of the catalyst used is preferably 10% or less, more preferably 5% or less, relative to the (meth)acrylic anhydride used. When the catalyst is used, if it exceeds the above range, it takes time to remove the catalyst, and the catalyst is likely to remain in the product, resulting in deterioration of properties.

[0075] In the reaction of the hydroxyl-containing phosphorus compound with (meth)acryloyl halide or / and (meth)acrylic anhydride, it is preferred to use an organic solvent as a reaction solvent and react in a solution. As the solvent that can be used, there is no particular limitation as long as it is not reactive with the phenol compound and (meth)acrylic halide or / and (meth)acrylic anhydride, and solvents such as tetrahydrofuran, dioxane, ethyl acetate, acetonitrile, benzene, toluene, xylene, methylene chloride, chloroform, carbon tetrachloride, dimethylformamide, dimethylacetamide, dimethyl sulfoxide, hexamethylphosphoric triamide, water, etc. can be cited, and these combinations can be used as needed.

[0076] In the reaction of the hydroxyl-containing phosphorus compound with the (meth)acrylic acid halide or / and (meth)acrylic anhydride, the reaction temperature is preferably -50°C to 150°C. If the reaction is carried out at a high temperature, the possibility of a polymerization reaction increases, so it is more preferably -25°C to 100°C. In addition, the reaction time is appropriately set according to the set reaction temperature, and is preferably set in the range of 1 hour to 48 hours.

[0077] The reaction of the hydroxyl-containing phosphorus compound with (meth) acrylic acid, (meth) acryloyl halide or (meth) acrylic anhydride can also be carried out in the presence of a polymerization inhibitor. By adding a polymerization inhibitor, the (meth) acrylic acid, (meth) acryloyl halide or (meth) acrylic anhydride provided for the reaction, or the (meth) acrylic acid ester as the target product, can be prevented from polymerizing and producing oligomers as a by-product. Regarding the polymerization inhibitor, known substances can be used without limitation, and organic compounds such as hydroquinone, hydroxy monomethyl ether, tert-butyl catechol, tert-butyl hydroquinone, 4-methoxyphenol, 4-methoxy-1-naphthol, phenothiazine, and copper compounds such as copper chloride and copper sulfide can be listed, and these can also be used in combination.

[0078] After completion of the reaction, the obtained reaction solution (reaction mixture) is subjected to distillation removal of the reaction solvent, solvent replacement, etc. as necessary, and is purified by washing with water or the like, activated carbon treatment, silica gel chromatography, etc., to extract the target (meth)acryloyl compound of the present invention.

[0079] Next, a flame-retardant resin composition prepared by blending the phosphorus-containing (meth)acryl composition of the present invention as an essential component with a curable resin or a thermoplastic resin will be described.

[0080] In the flame retardant resin composition of the present invention, the mixing ratio is not particularly limited. For example, 10 to 300 parts by weight of the phosphorus-containing (meth)acryl composition may be mixed with respect to 100 parts by weight of the total amount of the curable resin and the thermoplastic resin. Preferably, the ratio is 20 to 200 parts by weight, and more preferably, 50 to 150 parts by weight.

[0081] Examples of the curable resin include unsaturated polyester resins, curable maleimide resins, epoxy resins, polycyanate resins, phenol resins, and one or more vinyl compounds having one or more polymerizable unsaturated hydrocarbon groups in the molecule. Preferably, the resin is an epoxy resin or one or more vinyl compounds having one or more polymerizable unsaturated hydrocarbon groups in the molecule.

[0082] When the curable resin is an epoxy resin, it is preferably selected from one or more epoxy resins having two or more epoxy groups in one molecule. As the epoxy resin, cresol novolac epoxy resin, triphenylmethane epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, bisphenol A epoxy resin and bisphenol F epoxy resin can be listed. These can be used alone or in combination of two or more. It is believed that by using such an epoxy resin, the influence on the excellent dielectric properties and fluidity of the curable resin composition of the present invention can be limited to a minimum, and the heat resistance and adhesion of the cured product can be fully improved.

[0083] Furthermore, when epoxy resin is contained, a hardener may be used in addition to the epoxy resin. The hardener is not particularly limited, and examples thereof include phenol hardeners, amine compounds, amide compounds, acid anhydride compounds, naphthol hardeners, active ester hardeners, benzoxazine hardeners, and cyanate hardeners. These may be used alone or in combination of two or more.

[0084] Furthermore, when preparing epoxy resin, a hardening accelerator may be used as needed, such as amines, imidazoles, organic phosphines, Lewis acids, etc. The amount added is usually in the range of 0.2 to 5 parts by weight relative to 100 parts by weight of the epoxy resin.

[0085] When the curable resin is one or more vinyl compounds (hereinafter referred to as vinyl compounds) having one or more polymerizable unsaturated hydrocarbon groups in the molecule, the type is not particularly limited. That is, the vinyl compound can be cured by reacting with the phosphorus-containing (meth)acryloyl compound of the present invention to form a crosslink. More preferably, the compound has a carbon-carbon unsaturated double bond as the polymerizable unsaturated hydrocarbon group, and more preferably, the compound has two or more carbon-carbon unsaturated double bonds in the molecule.

[0086] The average number of carbon-carbon unsaturated double bonds per molecule of the vinyl compound as the curable resin (the number of vinyl groups (including substituted vinyl groups); also referred to as the number of terminal double bonds) varies depending on the Mw of the vinyl compound, and is preferably 1 to 20, and more preferably 2 to 18. If the number of terminal double bonds is too small, it tends to be difficult to obtain sufficient heat resistance as the heat resistance of the cured product. Moreover, if the number of terminal double bonds is too large, the reactivity becomes too high, and there may be undesirable situations such as decreased storage stability of the curable resin composition or decreased fluidity of the curable resin composition.

[0087] As the vinyl compounds, triallylisocyanurate (TAIC) and other triallyl isocyanurate compounds, modified polyphenylene ether (PPE) with (meth) acryloyl or styrene modified ends, multifunctional (meth) acrylate compounds having two or more (meth) acryloyl groups in the molecule, vinyl compounds (multifunctional vinyl compounds) having two or more vinyl groups in the molecule such as polybutadiene, and vinylbenzyl compounds such as styrene and divinylbenzene, etc. can be cited. Among them, compounds having two or more carbon-carbon double bonds in the molecule are preferred, and specifically TAIC, multifunctional (meth) acrylate compounds, modified PPE resins, multifunctional vinyl compounds, and divinylbenzene compounds can be cited. It is believed that if these are used, crosslinking will be better formed by the curing reaction, and the heat resistance of the cured product of the curable resin composition can be further improved. Moreover, these can be used alone or in combination of two or more. Moreover, compounds having one carbon-carbon unsaturated double bond in the molecule can also be used in combination. Examples of the compound having one carbon-carbon unsaturated double bond in the molecule include compounds having one vinyl group in the molecule (monovinyl compounds) and the like.

[0088] Examples of the thermoplastic resin include polystyrene, polyphenylene ether resin, polyetherimide resin, polyethersulfone resin, polyphenylene sulfide (PPS) resin, polycyclopentadiene resin, polycycloolefin resin, or known thermoplastic elastomers (e.g., styrene-ethylene-propylene copolymer, styrene-ethylene-butylene copolymer, styrene-butadiene copolymer, styrene-isoprene copolymer, hydrogenated styrene-butadiene copolymer, hydrogenated styrene-isoprene copolymer, etc.), or rubbers (e.g., polybutadiene, polyisoprene). Unmodified or modified polyphenylene ether resin and hydrogenated styrene-butadiene copolymer are preferred.

[0089] In the flame-retardant resin composition of the present invention, a free radical polymerization initiator (polymerization catalyst or cross-linking agent) that generates free radicals by light and / or heat may also be formulated. As the photopolymerization initiator, for example, benzoins such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, and benzoin isobutyl ether can be listed; acetophenones such as acetophenone, 2,2-diethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 2-hydroxy-2-methyl-phenylpropane-1-one, diethoxyacetophenone, 1-hydroxycyclohexyl phenyl ketone, and 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one; 2- Anthraquinones such as ethyl anthraquinone, 2-tert-butyl anthraquinone, 2-chloroanthraquinone, and 2-amyl anthraquinone; thioxanthones such as 2,4-diethyl thioxanthone, 2-isopropyl thioxanthone, and 2-chlorothioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 4,4'-dimethylaminobenzophenone; phosphine oxides such as 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, etc. Examples of the thermal radical initiator include benzoyl peroxide, cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, 2,5-dimethyl-2,5-di(tert-butylperoxide)hexyne-3, di-tert-butyl peroxide, tert-butyl cumyl peroxide, 1,3-bis(butylperoxide isopropyl)benzene, α,α'-bis(tert-butylperoxide meta-isopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxide)hexane, dicumyl peroxide, di-tert-butyl peroxide isophthalate, tert-butyl peroxide benzoate, 2,2-bis(tert-butylperoxide)butane, 2,2-bis(tert-butylperoxide)octane, 2,5-dimethyl-2,5-di(benzoylperoxide)hexane, bis(trimethylsilyl)peroxide, trimethylsilyltriphenylsilyl peroxide and the like peroxides, but are not limited thereto. Furthermore, although not a peroxide, 2,3-dimethyl-2,3-diphenylbutane can also be used as a radical polymerization initiator. However, the invention is not limited to these examples, and two or more radical initiators may be used in combination.

[0090] The amount of the radical polymerization initiator added is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, based on 100 parts by weight of the resin component.

[0091] The flame-retardant resin composition of the present invention must contain a phosphorus-containing (meth)acryl composition having two or more different chemical structures represented by the general formula (1) as a reactive flame retardant, and the phosphorus content in the flame-retardant resin composition is preferably 0.5 wt % to 5.0 wt %, and more preferably 1.0 wt % to 4.0 wt %.

[0092] Fillers can be formulated in the flame retardant resin composition of the present invention. As fillers, fillers added to improve heat resistance or flame retardancy can be cited, and known fillers can be used, but are not particularly limited. Moreover, by containing fillers, heat resistance, dimensional stability or flame retardancy can be further improved. Specifically, metal oxides such as silicon dioxide such as spherical silicon dioxide, aluminum oxide, titanium oxide, and mica, metal hydroxides such as aluminum hydroxide and magnesium hydroxide, talc, aluminum borate, barium sulfate, and calcium carbonate can be cited. When using metal hydroxides such as aluminum hydroxide and magnesium hydroxide, they act as flame retardant aids and flame retardancy can be ensured even if the phosphorus content is low. Among them, silicon dioxide, mica, and talc are preferably used, and spherical silicon dioxide is more preferably used. Moreover, these can be used alone or in combination of two or more.

[0093] The filler may be used directly or may be a filler surface-treated with a silane coupling agent such as an epoxysilane type or an aminosilane type. As the silane coupling agent, from the viewpoint of reactivity with a free radical polymerization initiator, a vinylsilane type, a methacryloxysilane type, an acryloxysilane type, and a styrylsilane type silane coupling agent is preferred. As a result, the bonding strength with the metal foil or the interlayer bonding strength between the resins is improved. Furthermore, the silane coupling agent may be added and used by an integral blending method rather than a method of pre-surface-treating the filler.

[0094] The content of the filler is preferably 10 to 200 parts by mass, more preferably 30 to 150 parts by mass, based on 100 parts by mass of the total solid content excluding the filler (including organic components such as monomers and flame retardants, excluding the solvent).

[0095] The flame retardant resin composition of the present invention may further contain additives other than those mentioned above. Examples of the additives include defoamers such as silicone defoamers and acrylate defoamers, heat stabilizers, antistatic agents, ultraviolet absorbers, dyes or pigments, lubricants, dispersants such as wetting dispersants, and the like.

[0096] The cured product obtained by curing the flame retardant resin composition of the present invention can be used as a molded product, a laminated product, an injection molded product, an adhesive, a coating film, or a film. For example, the cured product of the semiconductor sealing material is an injection molded product or a molded product. As a method for obtaining the cured product for the above-mentioned purpose, the curable resin composition can be molded using an injection molding machine, a transfer molding machine, an injection molding machine, etc., and then heated at 80°C to 230°C for 0.5 hours to 10 hours to obtain the cured product.

[0097] The flame retardant resin composition of the present invention can also be used as a prepreg. When manufacturing a prepreg, it can be prepared as a varnish for the purpose of being impregnated in a substrate (fibrous substrate) for forming a prepreg or for the purpose of making a circuit substrate material for forming a circuit substrate, thereby making a resin varnish. This resin varnish is suitable for circuit substrate purposes and can be used as a circuit substrate material varnish. In addition, the use of the circuit substrate material mentioned here can specifically include a printed wiring substrate, a printed circuit board, a flexible printed wiring board, a layer-increasing wiring board, etc.

[0098] The organic solvent used for the resin varnish is not particularly limited as long as it does not hinder the curing reaction. For example, ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as ethyl acetate, propyl acetate, and butyl acetate; polar solvents such as dimethylacetamide and dimethylformamide; aromatic hydrocarbon solvents such as toluene and xylene, etc., and these can be used alone or in combination of two or more. From the perspective of dielectric properties, aromatic hydrocarbons such as benzene, toluene, and xylene are preferred.

[0099] When preparing the resin varnish, the amount of the organic solvent used is preferably 5 to 900 parts by weight, more preferably 10 to 700 parts by weight, and particularly preferably 20 to 500 parts by weight, based on 100 parts by weight of the curable resin composition of the present invention.

[0100] As the substrate used when making the prepreg, known materials can be used, for example, glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, paper and other substrates can be used alone or in combination of two or more. For these substrates, a coupling agent can be used for the purpose of improving the adhesion between the resin and the substrate interface as required. As the coupling agent, a common coupling agent such as a silane coupling agent, a titanate coupling agent, an aluminum coupling agent, a zirconium aluminum coupling agent, etc. can be used.

[0101] As a method for obtaining a prepreg, there can be cited a method of impregnating the resin varnish into a substrate and then drying it. The impregnation is performed by dipping, coating, etc. The impregnation can be repeated multiple times as needed, and at this time, a plurality of solutions with different compositions or concentrations can be used to repeatedly impregnate and adjust to the final desired resin composition and resin amount. After impregnation, the prepreg can be obtained by heating and drying at 100°C to 180°C for 1 minute to 30 minutes. Here, the amount of resin in the prepreg is preferably set to 30% by weight to 80% by weight of the resin component.

[0102] The curable resin composition of the present invention can also be used as a laminate. When a prepreg is used to form a laminate, one or more prepregs are stacked, and a metal foil is arranged on one side or both sides to form a laminate, and the laminate is heated and pressurized to be laminated and integrated. Here, as the metal foil, copper, aluminum, brass, nickel, etc., single, alloy, or composite metal foil can be used. As the conditions for heating and pressurizing the laminate, it is sufficient to adjust the heating and pressurization appropriately under the conditions for curing the curable resin composition. However, if the pressurization pressure is too low, there will be residual bubbles inside the obtained laminate and the electrical properties will decrease. Therefore, it is preferred to pressurize under conditions that satisfy the formability. For example, the temperature can be set to 180°C to 250°C, and the pressure can be set to 49.0N / cm 2 ~490N / cm 2 (5kgf / cm 2 ~50kgf / cm 2 ), and the heating and pressing time is set to 40 minutes to 240 minutes. The single-layer laminate obtained in the above manner can be used as an inner layer material to make a multilayer board. In the above case, the laminate is firstly formed with a circuit by an additive method or a subtractive method, and the surface of the formed circuit is treated with an acid solution to perform a blackening treatment to obtain an inner layer material. On the circuit forming surface on one side or both sides of the inner layer material, an insulating layer is formed by using a resin sheet, a metal foil with resin, or a prepreg, and a conductor layer is formed on the surface of the insulating layer to form a multilayer board.

[0103] Furthermore, the curable composition of the present invention can also be used for a build-up film. A method for producing a build-up film from the resin composition of the present invention can include, for example, a method of applying the resin varnish on a support film and drying it to form a film-like insulating layer. The film-like insulating layer thus formed can be used as a build-up film for a multilayer printed wiring board.

[0104] [Example]

[0105] Next, the present invention will be described with reference to Examples, but the present invention is not limited thereto. Parts in each example are parts by weight.

[0106] In addition, the physical property measurement in the synthesis examples and working examples was performed by the method shown below.

[0107] (1) Phosphorus content: Sulfuric acid, hydrochloric acid and perchloric acid are added to the sample, heated and wet incinerated to convert all phosphorus atoms into orthophosphoric acid. Metavanadate and molybdate are reacted in a sulfuric acid acid solution, and the absorbance of the generated phosphovanadomolybdic acid complex at 420 nm is measured. The phosphorus atom content calculated based on a calibration curve prepared in advance using potassium dihydrogen phosphate is expressed in %.

[0108] (2) Solvent solubility: In a varnish adjusted to 50% by mass solid content using toluene as a solvent, those that did not precipitate after one week were rated as ○, and those that precipitated were rated as ×. Those that did not produce a methacryloyl compound were rated as -.

[0109] (3) Glass transition temperature: measured by differential scanning calorimetry at a heating rate of 10° C. / min and determined from the baseline shift.

[0110] (4) Relative dielectric constant and dielectric loss tangent: According to IPC-TM-6502.5.5.9, the dielectric constant and dielectric loss tangent at a frequency of 10 GHz were determined using a material analyzer (manufactured by Agilent Technologies) using a split postdielectric resonator (SPDR) method.

[0111] (5) Flame retardancy: evaluated by the vertical method in accordance with UL94. The evaluation was described as V-0, V-1, or V-2.

[0112] (6) HPLC (High-speed liquid chromatography): Using 0.5% phosphoric acid aqueous solution and acetonitrile as eluents, gradient elution was performed from 40% acetonitrile to 100% in 30 minutes, and the measurement was performed at a flow rate of 1.0 ml using LC-20A manufactured by Shimadzu Corporation. The detector used a photodiode array detector to detect the peak of each component at a wavelength of 210 nm. The column temperature was 40° C., and the column used was Cadenza CD-C18 manufactured by Imtakt.

[0113] (Synthesis example 1)

[0114] In a glass separable flask including a stirring device, a thermometer, a cooling tube, and an oxygen introduction device, 340 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and 660 parts of toluene were placed and dissolved at 80°C. While paying attention to the heat generated by the reaction, 245 parts of 1,4-naphthoquinone were added in batches. The reaction was continued, and the temperature was raised to 110°C, and the reaction was further carried out. After 3 hours, a slurry solution with dark brown crystals precipitated was obtained. The crystals were separated by filtration and dispersed in 500 parts of methanol. After this operation was performed three times, the mixture was dried in a hot air circulation oven to obtain a light yellow powder of phosphorus-containing phenol compound 10-(2,5-dihydroxynaphthyl)-10H-9-oxa-10-phosphaphenanthrene-10-oxide (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide-naphthoquinone (DOPO-NQ)).

[0115] [Chemistry 8]

[0116]

[0117] (Synthesis example 2)

[0118] The same apparatus as in Synthesis Example 1 was used, and except that 320 parts of diphenylphosphine oxide was used instead of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, the same operation as in Synthesis Example 1 was performed to obtain a phosphorus-containing phenol compound 2-diphenylphosphineoxide-1,4-naphthalenediol (diphenylphosphineoxide-naphthoquinone (DPO-NQ)) as a pale yellow powder.

[0119] [Chemistry 9]

[0120]

[0121] (Synthesis example 3)

[0122] Using the same apparatus as in Synthesis Example 2 and except that 189 parts of toluquinone was used instead of 1,4-naphthoquinone, the same operation as in Synthesis Example 1 was carried out to obtain a phosphorus-containing phenol compound diphenylphosphine oxide-toluquinone (DPO-TQ) as a pale yellow powder.

[0123] [Chemistry 10]

[0124]

[0125] Example 1

[0126] In a separable flask equipped with a stirrer, a nitrogen inlet pipe, a reflux pipe, and a thermometer, 25 parts of 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (HCA-HQ, a product of Sanko Co., Ltd.) as a hydroxyl-containing phosphorus compound and 25 parts of DOPO-NQ obtained in Synthesis Example 1 were placed.

[0127] [Chemistry 11]

[0128]

[0129] 50 parts of toluene as a solvent was dispersed. 2 parts of 4-dimethylaminopyridine (manufactured by Tokyo Chemical Industry Co., Ltd.) and 32 parts of triethylamine (manufactured by Tokyo Chemical Industry Co., Ltd.) were added. 52 parts of methacrylic anhydride was added dropwise while paying attention to the heat generated by the reaction.

[0130] [Chemistry 12]

[0131]

[0132] The reaction was carried out. After the disappearance of the raw material peak and the completion of methacrylation were confirmed by HPLC tracking, the triethylamine was removed under reduced pressure, and 1 part of methanol was added to decompose the remaining methacrylic anhydride. Methacrylic acid and methyl methacrylate were removed by washing with water, and a 50% toluene solution of non-volatile components was obtained by dehydration, filtration and concentration. The obtained methacrylic compound is two components, and the methacrylic acid ester of HCA-HQ and the methacrylic acid ester of DOPO-NQ are 44.6 to 55.4 in area %. The phosphorus content is 6.0% relative to the solid content. There is no precipitation in the obtained varnish.

[0133] Example 2

[0134] The same apparatus as in Example 1 was used, and 25 parts of DPO-NQ obtained in Synthesis Example 2, 25 parts of DOPO-NQ obtained in Synthesis Example 1, and

[0135] [Chemistry 13]

[0136]

[0137] The same operation was carried out except that 53 parts of methacrylic anhydride was added to obtain a toluene solution with a nonvolatile content of 50%. Figure 1The obtained methacryloyl compound consisted of two components, with the area % ratio of DPO-NQ methacrylate to DOPO-NQ methacrylate being 50.6 to 49.4. The phosphorus content was 6.1% relative to the solid content. The obtained varnish contained no precipitation.

[0138] Example 3

[0139] The same apparatus as in Example 1 was used, and 48 parts of DPO-TQ obtained in Synthesis Example 3 as the hydroxyl-containing phosphorus compound,

[0140] [Chemistry 14]

[0141]

[0142] The same operation was performed except that 70 parts of toluene and 103 parts of methacrylic anhydride were added to obtain a toluene solution containing 50% of nonvolatile matter. The obtained methacryloyl compound was three components of methacrylic acid ester isomers of DPO-TQ, and the area % ratios were 17.3, 46.9, and 35.8 from left to right in the above structural formula. The phosphorus content was 6.8% relative to the solid content. There was no precipitation in the obtained varnish.

[0143] Example 4

[0144] The same apparatus as in Example 1 was used, and 13 parts of diphenylphosphine oxide (DPO) and 13 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (HCA, a product of Sanko Co., Ltd.) as phosphorus-containing compounds were charged.

[0145] [Chemistry 15]

[0146]

[0147] 61 parts of toluene were heated and dissolved. 18 parts of 1,4-naphthoquinone (Naphthoquinone: NQ manufactured by Air-Water-Performance Chemical Co., Ltd.) were added while paying attention to the heat generation.

[0148] [Chemistry 16]

[0149]

[0150] To react and obtain two hydroxyl-containing phosphorus compounds. Next, the same operation was performed except that 1.6 parts of 4-dimethylaminopyridine, 26 parts of triethylamine and 41 parts of methacrylic anhydride were used to obtain a 50% toluene solution of non-volatile components. The obtained methacryloyl compound was two components, and the methacrylate of DPO-NQ and the methacrylate of HCA-NQ were 53.8 to 46.2 in terms of area %. The phosphorus content was 6.4% relative to the solid content. There was no precipitation in the obtained varnish.

[0151] Example 5

[0152] Using the same apparatus as in Example 1, 26 parts of HCA and 61 parts of toluene as a phosphorus-containing compound were charged and dissolved. 14.4 parts of toluquinone (TQ) was added to react to obtain two hydroxyl-containing phosphorus compounds.

[0153] [Chemistry 17]

[0154]

[0155] Next, the same operation was performed except that 1.6 parts of 4-dimethylaminopyridine, 26 parts of triethylamine and 41 parts of methacrylic anhydride were used to obtain a toluene solution containing 50% of nonvolatile matter. The obtained methacryloyl compound was two components of methacrylate isomers of HCA-TQ, and the area % ratio was 57.9 to 42.1 in the order from left to right of the following structural formula. The phosphorus content was 6.6% relative to the solid content. There was no precipitation in the obtained varnish.

[0156] [Chemistry 18]

[0157]

[0158] Example 6

[0159] Using the same apparatus as in Example 1, 30 parts of diphenylphosphine oxide (DPO) and 70 parts of toluene as a phosphorus-containing compound were charged and dissolved, and 17.8 parts of toluenequinone (TQ) were added to react to obtain three types of hydroxyl-containing phosphorus compounds.

[0160] [Chemistry 19]

[0161]

[0162] Next, the same operation was carried out except that 2.0 parts of 4-dimethylaminopyridine, 33 parts of triethylamine and 103 parts of methacrylic anhydride were used to obtain a toluene solution containing 50% of nonvolatile matter. The HPLC chart is shown in FIG. Figure 2The obtained methacryloyl compound was three components of methacrylate isomers of DPO-TQ, and the area % ratios were 16.7:47.2:36.1 from left to right in the structural formula. The phosphorus content was 6.7% relative to the solid content. There was no precipitation in the obtained varnish.

[0163] Example 7

[0164] The same apparatus as in Example 1 was used, and 26 parts of diphenylphosphine oxide (DPO) as a phosphorus-containing compound,

[0165] [Chemistry 20]

[0166]

[0167] 61 parts of toluene were dissolved. 2 parts of 1,4-naphthoquinone (NQ) and 13.8 parts of toluenequinone (TQ) were added.

[0168] [Chemistry 21]

[0169]

[0170] Then, a toluene solution with a nonvolatile content of 50% was obtained by the same operation except that 2.0 parts of 4-dimethylaminopyridine, 28 parts of triethylamine and 45 parts of methacrylic anhydride were used. The HPLC chart is shown in Figure 3 The obtained methacryloyl compound is composed of four components including methacrylate of DPO-NQ and isomers of methacrylate of DPO-TQ, and the area % ratios are 14.2: 42.4: 30.3: 13.1 in the order from the upper left to the right and then downward in the following structural formula. The phosphorus content is 6.9% relative to the solid content. There is no precipitation in the obtained varnish.

[0171] [Chemistry 22]

[0172]

[0173] Example 8

[0174] The same apparatus as in Example 1 was used, and 8 parts of HCA as a phosphorus-containing compound and 16 parts of diphenylphosphine oxide (DPO) were charged.

[0175] [Chemistry 23]

[0176]

[0177] 56 parts of toluene were dissolved. 13.9 parts of toluenequinone (TQ) were added.

[0178] [Chemistry 24]

[0179]

[0180] Then, the same operation was performed except that 2.0 parts of 4-dimethylaminopyridine, 26 parts of triethylamine and 40 parts of methacrylic anhydride were used to obtain a toluene solution with a non-volatile content of 50%. The HPLC chart is shown in Figure 4 The obtained methacrylic compound is composed of five components including methacrylic acid ester of HCA-TQ and isomers of methacrylic acid ester of DPO-TQ, and the area % ratios are 10.9: 38.3: 29.6: 1.3: 19.8 in the order from the upper left to the lower right of the following structural formula. The phosphorus content is 6.7% relative to the solid content. There is no precipitation in the obtained varnish. The structural formula of the obtained methacrylic resin is shown.

[0181] [Chemistry 25]

[0182]

[0183] Comparative Example 1

[0184] Using the same apparatus as in Example 1, 50 parts of toluene were added to 50 parts of HCA-HQ as a hydroxyl group-containing phosphorus compound and dispersed. The same operation was performed except that 2.2 parts of 4-dimethylaminopyridine, 34 parts of triethylamine, and 55 parts of methacrylic anhydride were used. However, after adding washing water, precipitation occurred and separation was not possible, and the methacryloyl compound could not be obtained.

[0185] Comparative Example 2

[0186] The same apparatus as in Example 1 was used, and the same operation was performed except that 50 parts of DOPO-NQ of Synthesis Example 1 as the hydroxyl-containing phosphorus compound, 50 parts of toluene, 2.0 parts of 4-dimethylaminopyridine, 27 parts of triethylamine, and 53 parts of methacrylic anhydride were used to obtain a toluene solution with a nonvolatile content of 50%. The HPLC chart is shown in Figure 5 The obtained methacryloyl compound was a single component. Precipitation was observed from the varnish on the next day. The solid component was separated by filtration and dried. The phosphorus content of the obtained solid matter was 6.0%.

[0187] Comparative Example 3

[0188] Using the same apparatus as in Example 1, 50 parts of DPO-NQ of Synthesis Example 2 as a hydroxyl-containing phosphorus compound and 50 parts of toluene were charged, dissolved, and dispersed. The same operation was performed except that 2.0 parts of 4-dimethylaminopyridine, 31 parts of triethylamine, and 50 parts of methacrylic anhydride were used. However, after charging with washing water, precipitation occurred and separation was not possible, and the methacryloyl compound could not be obtained.

[0189] Comparative Example 4

[0190] The same apparatus as in Example 1 was used, and 26 parts of Bz-HCA (Sanko Co., Ltd.) as a phosphorus-containing compound and 83 parts of toluene were charged and dissolved. 13.6 parts of 1,4-naphthoquinone were added for reaction to obtain a hydroxyl-containing phosphorus compound Bz-HCA-NQ. Next, 1.2 parts of 4-dimethylaminopyridine, 19 parts of triethylamine, and 29.4 parts of methacrylic anhydride were used, and the same operation was performed to obtain a non-volatile component 50% toluene solution. The obtained methacryloyl compound is one component. The phosphorus content is 5.2% relative to the solid content. Precipitation was observed from the varnish the next day.

[0191] [Chemistry 26]

[0192]

[0193] <Solubility test>

[0194] Table 1 shows the results of the solubility tests of the 50% toluene solutions prepared in Examples 1 to 8 and Comparative Examples 1 to 4.

[0195]

[0196] Examples 9 to 16, Comparative Examples 5 to 7

[0197] <Preparation of curable resin composition and production of cured product>

[0198] Varnish is prepared by mixing various ingredients in the proportions of Table 2 and Table 3, and applied to a polyethylene terephthalate resin film, dried in an oven at 130°C for 5 minutes, and a film of a resin composition is prepared. Next, the film is crushed and separated from the polyethylene terephthalate resin film to obtain a powder of the resin composition. Furthermore, this powder is sandwiched on a stainless steel mirror plate together with a spacer, and a vacuum oven is used to form a hardened sample at 210°C for 90 minutes. The hardened sample is used to evaluate the glass transition temperature or dielectric properties, and is shown in Table 2 and Table 3.

[0199]

[0200] [Table 3]

[0201] Comparative Example 5 Comparative Example 6 Comparative Example 7 OPE-2St 100 50.5 42.3 Resin of Comparative Example 2 49.5 Resin of Comparative Example 4 57.7 Perbutyl P 0.5 0.5 0.5 Glass transition temperature(℃) 156 207 175 Dielectric constant 2.7 2.8 2.7 Dielectric loss tangent 0.0036 0.0057 0.0062 Flame retardant NC V-0 V-0

[0202] <Preparation of flame retardant test pieces>

[0203] Varnish was prepared by mixing various components in the ratios of Tables 2 and 3, and the resin varnish was impregnated into glass cloth (manufactured by Nitto Bosho Co., Ltd.; 7628 type; model H258), followed by drying by heating at 130° C. for 5 minutes to obtain a prepreg.

[0204] The obtained 8 prepregs were stacked on top of copper foil (Mitsui Mining & Smelting Co., Ltd., 3EC-III, thickness 35 μm), and vacuum pressed at 2 MPa under the temperature conditions of 130°C × 15 minutes + 190°C × 80 minutes to obtain a 1.6 mm thick laminate. The copper foil was etched and cut to obtain a flame retardant test piece. The flame retardancy was evaluated using the flame retardant test piece, which is shown in Table 2 and Table 3.

[0205] [Industrial Applicability]

[0206] Since the phosphorus-containing (meth)acryl composition of the present invention contains at least two phosphorus-containing (meth)acryl compounds of different chemical structures, it has good solvent solubility and does not precipitate. When impregnated into a fiber base material or formed into a film, a material with a uniform composition can be obtained, thereby showing stable physical properties. Furthermore, by simultaneously producing two or more phosphorus-containing (meth)acryl compounds, there is no precipitation in the process and the desired phosphorus-containing (meth)acryl composition can be easily obtained.

Claims

1. A phosphorus-containing (meth)acryl composition, which is a composition of a phosphorus-containing (meth)acryl compound represented by the general formula (1), characterized in that: A phosphorus-containing (meth)acryloyl compound comprising at least two different chemical structures; [Chemistry 1] In the general formula (1), R 1 , R 2 , R 3 are independently hydrogen, hydroxyl or a group represented by -R, where R is a hydrocarbon group having 1 to 40 carbon atoms; R 1 , R 2 They may be the same or different and may form a ring structure together with the phosphorus atom; n is 0 or 1; X represents an aromatic hydrocarbon group having 6 to 20 carbon atoms, and m is 1 to 3.

2. The phosphorus-containing (meth)acryl composition according to claim 1, comprising at least 1 area % or more of each of at least two phosphorus-containing (meth)acryl compounds having different chemical structures.

3. A method for producing a phosphorus-containing (meth)acryl composition, which is a method for producing the phosphorus-containing (meth)acryl composition according to claim 1, characterized in that: Reacting two or more hydroxyl-containing phosphorus compounds represented by the general formula (2) with (meth)acrylic acid, (meth)acrylic anhydride or (meth)acryloyl halide compounds to (meth)acrylylate the two or more hydroxyl-containing phosphorus compounds; [Chemistry 2] R in the general formula (2) 1 , R 2 , X, n, and m have the same meanings as in the general formula (1).

4. The method for producing a phosphorus-containing (meth)acryl composition according to claim 3, characterized in that: After reacting the phosphorus-containing compounds represented by the general formula (3) with quinone compounds to obtain two or more hydroxyl-containing phosphorus compounds, the obtained two or more hydroxyl-containing phosphorus compounds are (meth)acrylated; [Chemistry 3] R in the general formula (3) 1 , R 2 and n have the same meanings as in the general formula (1).

5. A flame retardant resin composition, characterized in that The phosphorus-containing (meth)acryl composition according to claim 1 is prepared by mixing one or more of a thermosetting resin or a thermoplastic resin.

6. A prepreg, which is prepared by mixing the flame-retardant resin composition according to claim 5 into a fibrous base material and semi-curing the mixture.

7. A resin sheet obtained by applying the flame-retardant resin composition according to claim 5 onto a resin film and semi-curing the film. 8 . A cured product obtained by curing the flame-retardant resin composition according to claim 5 , the prepreg according to claim 6 , or the resin sheet according to claim 7 .

9. A laminate for an electronic circuit board, comprising the flame-retardant resin composition according to claim 5 as an essential component.